Molecular Epidemiology of Cross-Species Giardia duodenalis Transmission in Western Uganda - Johnston, Amanda R. (Public Library of Science, 2010)
BACKGROUND: Giardia duodenalis is prevalent in tropical settings where diverse opportunities exist for transmission between people and animals. We conducted a cross-sectional study of G. duodenalis in people, livestock, and wild primates near Kibale National Park, Uganda, where human-livestock-wildlife interaction is high due to habitat disturbance. Our goal was to infer the cross-species transmission potential of G. duodenalis using molecular methods and to investigate clinical consequences of infection. METHODOLOGY/PRINCIPAL FINDINGS: Real-time PCR on DNA extracted from fecal samples revealed a combined prevalence of G. duodenalis in people from three villages of 44/108 (40.7%), with prevalence reaching 67.5% in one village. Prevalence rates in livestock and primates were 12.4% and 11.1%, respectively. Age was associated with G. duodenalis infection in people (higher prevalence in individuals ≤15 years) and livestock (higher prevalence in subadult versus adult animals), but other potential risk factors in people (gender, contact with domestic animals, working in fields, working in forests, source of drinking water, and medication use) were not. G. duodenalis infection was not associated with gastrointestinal symptoms in people, nor was clinical disease noted in livestock or primates. Sequence analysis of four G. duodenalis genes identified assemblage AII in humans, assemblage BIV in humans and endangered red colobus monkeys, and assemblage E in livestock and red colobus, representing the first documentation of assemblage E in a non-human primate. In addition, genetic relationships within the BIV assemblage revealed sub-clades of identical G. duodenalis sequences from humans and red colobus. CONCLUSIONS/SIGNIFICANCE: Our finding of G. duodenalis in people and primates (assemblage BIV) and livestock and primates (assemblage E) underscores that cross-species transmission of multiple G. duodenalis assemblages may occur in locations such as western Uganda where people, livestock, and primates overlap in their use of habitat. Our data also demonstrate a high but locally variable prevalence of G. duodenalis in people from western Uganda, but little evidence of associated clinical disease. Reverse zoonotic G. duodenalis transmission may be particularly frequent in tropical settings where anthropogenic habitat disturbance forces people and livestock to interact at high rates with wildlife, and this could have negative consequences for wildlife conservation.